« L’écriture inclusive, je ne connais pas très bien… mais je déteste ! » - Tania Sauteur; Pascal Gygax; Julia Tibblin; Lucie Escasain; Sayaka Sato (Glad!)
Although gender inclusive writing is widely polarised in public opinion, the exact causes of reluctance towards its use are not always clear. We explore the link between attitudes towards inclusive writing and different factors, such as the level of linguistic or historical knowledge of inclusive writing. We also measured the political orientation of the respondents, as well as their views on the political dimension of language, in order to assess their relationships with attitudes towards inclusive writing. The results show that the more people have historical knowledge of inclusive writing, the more they believe that inclusive writing is a response to political injunctions. The results also show that the further to the right of the political spectrum people are, the less they know about inclusive writing (its tools as well as its history) and the more they reject it. The present study provides new insights - related in particular to knowledge - into the distrust expressed by a part of the population towards new language practices aiming at more equality.